Adverse Birth Outcomes associated with Antenatal Care among Mothers at Madhesh Province, Nepal: A Cross Sectional Study - Jitendra Kumar Singh; Dipendra Kumar Yadav; Niranjan Shrestha; Prakash Sharma; Saroj Yadav; Subodh Sharma; Rajesh Kumar Yadav (Janaki Medical College Journal of Medical Science, 2024)
Background & Objectives: High-quality antenatal care (ANC) plays a vital role in reducing maternal and neonatal mortality rates and enhancing health results, especially in low-income nations. Although various factors play a role in adverse birth outcomes, antenatal care (ANC) emerges as a crucial preventive measure. Therefore, this study was conducted to investigate factors that influence participation in antenatal care services and their association with adverse birth outcomes in Madhesh Province of Nepal. Materials and Methods: A quantitative cross-sectional study was conducted among mothers who delivered their baby at health care facilities of Madhesh Pradesh from July 2020 to January 2021. A total of 104 participants selected for the study. Structured questionnaire was used and face to face interview was carried out to obtain information from participants. SPSS software was used for the data analysis and multiple logistic regression analysis was performed. A p value of less than 0.05 is considered statistically significant. Results: Among 104 mother, 11 had an adverse birth outcome. Majority of pregnancy related characteristics and antenatal care during pregnancy were significantly associated with adverse birth outcomes. In terms of socioeconomic status, education (p=0.021) and occupation (p<0.0001) showed the significant association with adverse outcome in bivariate analysis. However, in multivariate analysis socio demographic factors such as mothers’ occupation (p=0.004) and antenatal care practice such as rest during pregnancy (p=0.023) remained statistically significant. Conclusion: Finding suggests that mothers’ occupation and rest during pregnancy were associated with adverse birth outcomes. Therefore, raising awareness through prenatal care educational programs may reduce the likelihood of adverse delivery outcomes.